(untitled) (Ágora Journal, 2026)
In early Rome, the regulation of sexual morality was closely linked to the authority of the pater familias, who could make use of the ius vitae ac necis in cases where a daughter’s impudicitia endangered the dignity and honour of the family. Valerius Maximus recounts two episodes, that of Atilius Filiscus and that of Pontius Aufidianus, which provide different approaches to the stricter or broader interpretation of the concept of iusta causa in the exercise of ius vitae ac necis over the filiae familiae.